2016
DOI: 10.1108/sampj-10-2014-0063
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory analysis of managerial perceptions of social and environmental reporting in China

Abstract: Purpose – This paper aims to determine the perceptions of managers in China with respect to the pressures for, and the purposes of, social and environmental reporting (SER) in the Chinese context. Design/methodology/approach – The authors interviewed 14 managers from nine different state-owned enterprises, all headquartered in Beijing. Interviews were conducted during 2009, the height of the period of growth in standalone corporate socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 38 publications
9
80
0
Order By: Relevance
“…Though some scholars argue that institutional pressure for demonstrating CSR is rather low in China (Liu & Anbumozhi, 2009), the implementation of the Green Credit Guidelines may have created institutional pressure on the Chinese financial sector. Other studies found that the Chinese government urges companies, such as banks, to take CSR seriously (Marquis & Qian, 2014), and that firms respond to this pressure through social and environmental reporting (Zhao & Patten, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Though some scholars argue that institutional pressure for demonstrating CSR is rather low in China (Liu & Anbumozhi, 2009), the implementation of the Green Credit Guidelines may have created institutional pressure on the Chinese financial sector. Other studies found that the Chinese government urges companies, such as banks, to take CSR seriously (Marquis & Qian, 2014), and that firms respond to this pressure through social and environmental reporting (Zhao & Patten, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Chinese banks take CSR seriously [82], and increase their green lending. Furthermore, their commercial borrowers also increase their environmental performance because of both institutional [83] and market pressure [28,84].…”
Section: Discussionmentioning
confidence: 99%
“…Adams and McNicholas (2007) examined the SOE that supplies water to urban populations in the State of Victoria (Australia). Regarding public services, several studies have focused on the environmental area of CSR [48,91,94]. Thus, Chun (2009) analysed and compared ethical values and environmentalism among employees of SOEs and private companies in China, One of the first descriptive articles to be published was a "research forum" presented by Roper and Baker (2011), which highlighted the need to reflect on CSR issues in SOEs because of the particular characteristics of these companies.…”
Section: The Practice Of Corporate Social Responsibility In State Ownmentioning
confidence: 99%